Geography of the Swiss Foundation Sector. Atlas and analysis of the Swiss public-benefit foundations, their spatial distribution, purpose categories and geographical spheres of activities. - Reynolds Schier, Irene (My University, 2020)
This thesis examines Swiss public-benefit foundations from a geographical point of view. It follows an interdisciplinary approach, bridging geographic and philanthropical concepts and conducting basic research as little is yet known regarding the geography of these foundations. First, the study systematically collects detailed data on the locations of the foundations. Secondly, it classifies the multitude of foundation purposes and notes their spatial distribution. Lastly, it poses questions on the geographical spheres of activities of the foundations and their engagement in Switzerland and abroad. The analysis, with the cut-off-date at the end of 2014, is based on 12,600 foundations, which were surveyed one by one. Over 100 maps in color complement the findings and create an atlas on the geography of the foundation landscape at a municipal, cantonal, national and international scale. Also, the foundation sectors in each of the 26 cantons are portrayed, emphasizing their diversity and distinctive spatial patterns. Finally, the thesis proposes that the Swiss foundation sector is deeply embedded in society and reflects the country’s natural geography, political and administrative frameworks, economic structures, and cultural and social traits of its cantons and municipalities. The findings of the thesis enhance the transparency of the foundation landscape and contribute to its better understanding.

Die Autorin untersucht Schweizer Gemeinnützige Stiftungen aus geografischer Sicht und folgt einem interdisziplinären Ansatz, der geographische und philanthropische Konzepte überbrückt und Grundlagenforschung betreibt, da über die Geographie dieser Stiftungen noch wenig bekannt ist. Zunächst sammelt die Studie systematisch detaillierte Daten über die Standorte der Stiftungen. Zweitens klassifiziert sie die Vielzahl der Gründungszwecke und notiert deren räumliche Verteilung. Schließlich stellt sie Fragen zu den geographischen Tätigkeitsbereichen der Stiftungen und deren Engagement im In- und Ausland. Die Analyse mit dem Stichtag Ende 2014 basiert auf 12.600 Stiftungen, die nacheinander befragt wurden. Über 100 Karten ergänzen die Funde und erstellen einen Atlas zur Geographie der Stiftungslandschaft auf kommunaler, kantonaler, nationaler und internationaler Ebene. Auch die Gründungssektoren in jedem der 26 Kantone werden dargestellt und betonen deren Vielfalt und unterschiedliche Raummuster. Schließlich schlägt die These vor, dass der Schweizer Stiftungssektor tief in der Gesellschaft verankert ist und die natürliche Geographie, die politischen und administrativen Rahmenbedingungen des Landes, die wirtschaftlichen Strukturen sowie die kulturellen und sozialen Merkmale seiner Kantone und Gemeinden widerspiegelt.
Keywords: Stiftung; Räumliche Verteilung; Raumwirkung; Raumbezug; Standortkarte; Kanton; Gemeinwohl; Gemeinnützigkeit; Tätigkeitsmerkmal; Tätigkeitsfeld; Organisationsform; Klassifizierung; Rahmenbedingung; Befragung; Stiftungswesen; Stiftungszweck; Philantropie; Non-Profit-Organisation